Arquitetura do passado como semente para o futuro - Cappelletti, Giulia (2022)
With the current event of globalization, capitalism and energy crisis it is possible to observe a growing trend towards rapid development and always control of cities and buildings. Such a circumstance will manifest itself quickly and the main purpose of the building purpose will be done immediately, with the aim of making the person immediately visible, the buildings and the immediate results and the comfort of the user is done immediately. There is a moment of rapid architecture consumption, since the construction of new buildings is initial every day, with quick objectives, to meet the expectations of the new mundane, cultural, social and necessary currents. fundamentals of the application of the fundamentals of bioclimate, a bioclimatic and specific movement of the architecture of vernacular architecture is manifested, precepts of architecture that carry in itself the fundamentals of the history of the human being have a common project to these fundamentals of bioclimatology. In this sense, this research aims to study the immigrant vernacular architecture of the region of Três Santas (ES) and the analysis of the bioclimatological principles applied therein. For this, an in loco survey was carried out in the delimited regions, with the objective of obtaining data referring to pre-selected vernacular specimens, based on location, nationality and construction period. Obtained in the field compared with research with references such as bioclimatic strategies during the theoretical references, allowed the understanding of the functioning functions of the buildings and the functioning data of the buildings, such as the security of the vernacular architecture of immigrant people. The results also generated suggestions related to possible starting points for research related to this topic.